2019
DOI: 10.3390/ijms20092107
|View full text |Cite
|
Sign up to set email alerts
|

UMP Kinase Regulates Chloroplast Development and Cold Response in Rice

Abstract: Pyrimidine nucleotides are important metabolites that are building blocks of nucleic acids, which participate in various aspects of plant development. Only a few genes involved in pyrimidine metabolism have been identified in rice and the majority of their functions remain unclear. In this study, we used a map-based cloning strategy to isolate a UMPK gene in rice, encoding the UMP kinase that phosphorylates UMP to form UDP, from a recessive mutant with pale-green leaves. In the mutant, UDP content always decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
(104 reference statements)
0
12
0
Order By: Relevance
“…The orthologous enzyme in rice is localized in chloroplasts and participates in RNA metabolism, and the corresponding loss-of-function mutants are pale green (Zhu et al, 2016;Chen et al, 2018a). Additionally, they contain less UDP and more UMP (Dong et al, 2019), suggesting that UMP phosphorylation in the chloroplast is functionally important. The phosphorylation of thymidine 59-monophosphate (TMP) is not catalyzed by UMKs but by a dedicated TMP kinase (TMK; Fig.…”
Section: The Generation Of Nucleoside Triphosphatesmentioning
confidence: 99%
“…The orthologous enzyme in rice is localized in chloroplasts and participates in RNA metabolism, and the corresponding loss-of-function mutants are pale green (Zhu et al, 2016;Chen et al, 2018a). Additionally, they contain less UDP and more UMP (Dong et al, 2019), suggesting that UMP phosphorylation in the chloroplast is functionally important. The phosphorylation of thymidine 59-monophosphate (TMP) is not catalyzed by UMKs but by a dedicated TMP kinase (TMK; Fig.…”
Section: The Generation Of Nucleoside Triphosphatesmentioning
confidence: 99%
“…Such upregulation of subunits of DNA-directed RNA polymerase may be explained by severe stress triggered by BMAA in nitrogen limitation conditions. It was demonstrated that the expression level of plant genes encoding rpoB and rpoC1 is induced by various stresses [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The content of uracil has been shown to significantly decrease in soybean (Glycine max) subjected to heat or drought stress [26]. Mutants of UMP kinase became more sensitive to cold stress in rice (O. sativa), as manifested by a reduction in Chl content and photosynthesis [27]. Thymine and guanosine are important components of DNA, and it has been exhibited that thymine has a positive effect on drought tolerance of wheat (Triticum aestivum), as drought-tolerant cultivars had a higher level of thymine than that of drought-sensitive cultivars [28,29].…”
Section: Discussionmentioning
confidence: 99%